Drug Smuggling in Indonesia by Foreign Nationals: A Review through the Lens of Organized Transnational Crime Theory - Prasetyo, Dimas Putra Catur; Yeni Widowaty (Jurnal Penegakan Hukum dan Keadilan, 2026)
Efforts to smuggle narcotics (drugs/dangerous substances) into Indonesia from abroad have not stopped or decreased; in fact, they tend to be stable without any significant decrease. Indonesia is still a fertile field for narcotics smugglers with various modes, especially narcotics brought by foreign nationals. The proposed problem formulation is as follows: What factors increase the occurrence of narcotics smuggling by foreign nationals when viewed from the theory of criminal organizations? Second, how will the government's efforts to combat transnational narcotics smuggling be in the future? Related to the theory of transnational criminal organizations and the steps taken by the Indonesian government in overcoming and eradicating organized transnational narcotics smuggling crimes committed by foreign nationals. The author's analysis method in this study is normative legal research examining applicable laws, literature, and norms related to the problems studied, using secondary, primary, and tertiary materials. The global crisis has encouraged the rise of the narcotics business, which is linked to the theory of transnational organized crime related to syndicate organizations, as can be seen in the still high number of narcotics smuggling cases in Indonesia, amounting to 240 cases from 2024 to March 2025. The Indonesian government should take the following steps to overcome this crime: strengthen human resources, conduct counseling and surveys, support technological facilities and infrastructure, increase cooperation with other countries, and involve the community in eradicating narcotics smuggling.